Degree of bone marrow oedema in sacroiliac joints of patients with axial spondyloarthritis is linked to gut inflammation and male sex: results from the GIANT cohort. Issue 6 (25th November 2013) - Van Praet, Liesbet; Jans, Lennart; Carron, Philippe; Jacques, Peggy; Glorieus, Elien; Colman, Roos; Cypers, Heleen; Mielants, Herman; De Vos, Martine; Cuvelier, Claude; Van den Bosch, Filip; Elewaut, Dirk
Abstract : Introduction: Bone marrow oedema (BMO) of the sacroiliac joints (SIJs) is a hallmark of axial spondyloarthritis (SpA). However, the relationship between the extent of BMO and disease phenotype is poorly understood. Objective: To assess the link between BMO of the SIJs and gut inflammation. We have also evaluated the correlation between BMO and established disease activity parameters. Methods: Sixty-eight patients with axial SpA from the Gent Inflammatory Arthritis and spoNdylitis cohorT underwent ileocolonoscopy and MRI of the SIJs. Histopathological analysis and SPondyloArthritis Research Consortium of Canada (SPARCC) scores were performed. Results: A significant higher SPARCC score (median (range)) was observed in axial SpA patients showing chronic gut inflammation (16.9 (3.8–68.3)) compared with axial SpA patients showing normal gut histology (9.8 (0.0–45.0); p<0.05). In a multiple linear regression model, we identified, besides chronic gut inflammation (effect size of 11.3, 95% CI (2.1 to 20.4)), male sex (effect size of 10.5, 95% CI (3.3 to 17.8)) to be independently associated to the extent of BMO. There was a low to moderate correlation between the degree of BMO and C-reactive protein(r=0.39, p=0.002) and Ankylosing Spondylitis Disease Activity Score (r=0.35, p=0.007). Conclusions: Higher degrees of BMO were observed in patients showing chronic gut inflammation. These data solidify a link between mucosal inflammation and progressive disease in axial SpA.